Differential expressions of bilaterally unerupted supernumerary teeth - S Masih; H S Sethi; N Singh; A M Thomas (Wolters Kluwer Medknow Publications, 2011)
This article presents a case of bilateral unerupted supernumerary teeth in the mandibular premolar region. Surgical removal of the right-sided supernumerary tooth had to be carried out as it was impeding the eruption of the mandibular first premolar. However, its supernumerary antimere, lay dormant.